Orthotopic MAINZ pouch bladder substitution – long-term follow-up - Bröder, Saskia (Cent European J Urol, 2021)
INTRODUCTION: After radical cystectomy, orthotopic neobladder is one surgical strategy for urinary diversion. To assess the usefulness of an operation, long-term data are essential. We examined long-term complications and continence rates of orthotopic ileocecal (MAINZ pouch) bladder substitution. MATERIAL AND METHODS: Between 1986 and 2011, 193 patients underwent orthotopic MAINZ pouch bladder substitution. Until July 2000, ureter implantation was performed into the ascending colon through a submucosal tunnel technique (Goodwin-Hohenfellner). After July 2000, ureters were implanted into the terminal Ileum using the ileocecal valve to prevent reflux: the left spatulated ureter by an end-to-end (Wallace) and the right ureter by an end-to side technique (Nesbit). Surgical and medical follow-up reports were evaluated and a recent follow-up was obtained by a questionnaire. RESULTS: Median follow-up in 183 patients was 72 months (1–336). A total of 74 patients (38%) died during the follow-up. A surgical intervention was required in 26 out of 193 patients with early complications while 45 out of 183 patients had late and 17 patients had both, early and late complications. Ureteral stenosis was found in 13% of submucosal implanted ureters, 13% with the Wallace technique, and 3.6% with the Nesbit technique. In total, 66 patients responded to the questions concerning long-term continence (minimal follow-up >2 years). Overall, 84.8% were completely continent, 1.6%, reported grade I and 9.8% grade II stress incontinence. CONCLUSIONS: The long-term continence and complication rates are comparable to those of other types of orthotopic bladder substitution. Orthotopic MAINZ pouch procedure can be considered as one of the options for orthoptic diversion, which stands the test of time.